Neighbors denounce the Turkish bolichero. Territorial conflicts between Arab merchants and local settlers in the northwest of Chubut (1910-1955) (Quinto Sol, 2021)
This article studies different territorial conflicts between Arab merchants and neighboring indigenous peoples, creoles, and immigrants in the northwest of the National Territory of Chubut during the first half of the 20th century. Different cases are followed-up through documents produced by the Dirección Nacional de Tierras (National Land Directorate) and the Chubut governorate, advancing in generalizations that allow discussing the speeches that have simplified the processes of land appropriation. Based on these cases, we propose to review the usual historiographic periodization about the beginning of the processes of enclosure and the territorial conflicts that staged the Syrian-Lebanese immigrants. It is argued that the Arab merchants, by introducing perimeter fences, broke a previous territorial ordering based on occupations that were not delimited and that were generally regulated by neighborhood agreements. The historiographical reconstruction shows that the Syrian-Lebanese bolicheros managed to maintain and expand their enclosures after long-term administrative processes, gradually imposing a new order marked by private appropriation of land.
Keywords: migratory studies; syrian-lebanese; agrarian history; land